Modifying Graft-versus-Host Disease in a Humanized Mouse Model by Targeting Macrophages or B-Cells - Marieke C. H. Hogenes; Suzanne van Dorp; Joyce van Kuik; Filipa R. P. Monteiro; Natalie ter Hoeve; Liane Guedes; Marijke R. van Dijk; Anton C. Martens; Roel A. de Weger (Journal of Immunology Research)
Humanized mouse models can well be modified to study specific aspects of Graft-versus-Host Disease (GvHD). This paper shows the results of both macrophage depletion and (early) B-cell depletion in a humanized mouse model using RAG2-/-γc-/- mice injected with HuPBMCs. Macrophage depletion showed a significant decrease in survival and also lead to a change in the histomorphology of the xenogeneic reaction. Higher levels of infiltrating B-cells were observed in various organs of mice depleted for macrophages. With (early) B-cell depletion using Rituximab, a clear improvement on clinical symptoms was observed, even when probably only inactivated B-cells were deleted. However, the histological examinations only showed a significant morphological effect on liver fibrosis. This may be related to a difference in the mRNA levels of TGF-β. Also, lower mRNA levels of Tregs in some organs were observed after Rituximab treatment, which contradicts that a higher number of Tregs would always be related to less severe GvHD. Our data show that both macrophage depletion and (early) B-cell depletion in a xenogeneic mouse model can influence the clinical, histological, and cytokine production of a GvHD response.